PELATIHAN SPSS PADA MAHASISWA TINGKAT AKHIR JURUSAN AKUNTANSI DAN MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIYATAMANDALA - Andres Dharma Nurhalim; Shandy Puspita (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2022)
Research data processing becomes a frightening specter for students because of limited knowledge about data processing applications and how to process the data itself. The purpose of this service activity is to increase students' understanding, knowledge and skills in using applications/software for quantitative data processing, namely SPSS. The SPSS used in this service activity uses version 25 which is a software program that aims to analyze data and perform statistical calculations both parametric and non-parametric. This service activity uses lecture, discussion and direct practice/practice methods. The target audience for this activity is final year students who are preparing a thesis